Comparison of a Ring On-Chip Network and a Code-Division Multiple-Access On-Chip Network. (5th April 2007) - Wang, Xin; Nurmi, Jari
Abstract : Two network-on-chip (NoC) designs are examined and compared in this paper. One design applies a bidirectional ring connection scheme, while the other design applies a code-division multiple-access (CDMA) connection scheme. Both of the designs apply globally asynchronous locally synchronous (GALS) scheme in order to deal with the issue of transferring data in a multiple-clock-domain environment of an on-chip system. The two NoC designs are compared with each other by their network structures, data transfer principles, network node structures, and their asynchronous designs. Both the synchronous and the asynchronous designs of the two on-chip networks are realized using a hardware-description language (HDL) in order to make the entire designs suit the commonly used synchronous design tools and flow. The performance estimation and comparison of the two NoC designs which are based on the HDL realizations are addressed. By comparing the two NoC designs, the advantages and disadvantages of applying direct connection and CDMA connection schemes in an on-chip communication network are discussed.